2014
DOI: 10.1136/bmjqs-2014-003005
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary, multifaceted improvement initiative to eliminate mislabelled laboratory specimens at a large tertiary care hospital

Abstract: A multidisciplinary unit specific approach using performance improvement methodologies focusing on human factors can reliably and sustainably reduce the rate of mislabelled laboratory specimens in a large tertiary care hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…The teams met on regular basis to develop collaborative approaches according to the organizational needs that were acceptable and sustainable to staff in order to reduce specimen identification errors. The interventions were targeted to the general population in five studies 1518, 20 , children and adults in one study, 19 and in one study the target population was newborn children. 11 The total evidence was derived from varied types of healthcare settings, i.e., three studies 1517 were conducted in entire facilities including different settings such as inpatient, ambulatory, surgical services areas, emergency department, ICU, general care unit, one study 19 in inpatient setting, one 20 in surgical unit, one 18 in dermatology unit, and one 11 in pediatric department.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The teams met on regular basis to develop collaborative approaches according to the organizational needs that were acceptable and sustainable to staff in order to reduce specimen identification errors. The interventions were targeted to the general population in five studies 1518, 20 , children and adults in one study, 19 and in one study the target population was newborn children. 11 The total evidence was derived from varied types of healthcare settings, i.e., three studies 1517 were conducted in entire facilities including different settings such as inpatient, ambulatory, surgical services areas, emergency department, ICU, general care unit, one study 19 in inpatient setting, one 20 in surgical unit, one 18 in dermatology unit, and one 11 in pediatric department.…”
Section: Resultsmentioning
confidence: 99%
“…Results from all studies were statistically significant but for one study 17 due to the limited information available to calculate the significance of results. The strength of the effect size was considered ‘substantial’ from four studies 11, 15, 17, 19 ‘moderate’ from two studies, 16, 20 and ‘minimal’ for one study 18 . Overall data showed that improved communication and collaborative efforts by the clinical and laboratory staff (e.g., development of standardized policies and practices for specimen labeling and organizational workflow chart to determine strategies to check for any scope of errors, establishment of processes to check specimen slips for missing collection dates) resulted in significant decrease in the rate of specimen identification errors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because workarounds and process variations can pose hazards, reducing these by implementing standard policies and procedures is important to mitigate risks. Perioperative leaders also should address human and environmental factors . Efficiency is important, but never at the expense of patient safety.…”
Section: Surgical Specimen Errorsmentioning
confidence: 99%
“…Various errors can occur with specimen management during operative and other invasive procedures. Researchers categorize surgical specimen errors according to three phases of the specimen management process: preanalytic (ie, the time the specimen is in the OR and is transported to the pathology department), analytic (ie, the time from when pathology department personnel receive the specimen through specimen analysis), and postanalytic (ie, the time from specimen analysis to the reporting of results) (Figure ) . Most surgical specimen errors occur during the preanalytic phase and are preventable .…”
mentioning
confidence: 99%